1978
DOI: 10.1080/00063657809476600
|View full text |Cite
|
Sign up to set email alerts
|

The winter distribution of Purple Sandpipers in Britain

Abstract: A survey of numerical data from regional sources suggests that the British wintering population of Purple Sandpipers is between 14,500 and 23,000 birds, mainly concentrated in the north-east.THE PURPLE SANDPIPER Calidris maritima will winter in more northern latitudes than any other species of wader. It has an almost circumpolar Holarctic breeding distribution, and is present all year in those coastal parts of this range which remain ice-free in winter. Elsewhere it is migratory, and the wintering range extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…The main concentration of the wintering population of 14500-23000 birds is in the north-east (Atkinson et al 1978). The main concentration of the wintering population of 14500-23000 birds is in the north-east (Atkinson et al 1978).…”
Section: Introductionmentioning
confidence: 97%
“…The main concentration of the wintering population of 14500-23000 birds is in the north-east (Atkinson et al 1978). The main concentration of the wintering population of 14500-23000 birds is in the north-east (Atkinson et al 1978).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have suggested that site fidelity is high (though most have not reported return rates 22,24,34 ). One study in Germany found that 79-83% of colourringed birds returned to the same wintering area after the breeding season.…”
Section: Site-fidelity Between Winters and Survivalmentioning
confidence: 99%
“…Site-fidelity between winters has been recorded in a number of studies of both Turnstones [18][19][20][21] and Purple Sandpipers 22,24,34,35 (also K-B. Strann, pers.…”
Section: Site-fidelity Between Winters and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are sedentary during winter and also very loyal to wintering areas between years (Atkinson, Davies & Prater 1978, Atkinson et al 1981. Four Purple Sandpipers from breeding areas in SW Norway have been found wintering on the rocky shore of the Forth.…”
Section: Curlewmentioning
confidence: 98%